A dataset on knowledge creation and patenting by European Higher Education Institutions (KC-HEI) - Aleksandra Parteka; Piotr Płatkowski; Sabina Szymczak; Joanna Wolszczak-Derlacz (Gdansk University of Technology, Faculty of Management and Economics, 2024)
This paper describes the construction of a microlevel database on knowledge creation by higher education institutions (KC-HEI), accompanying the Global Knowledge InputOutput database (KIO, Davies et al., 2023). The database was created as part of Project Rethink GCS. KC-HEI links PATSTAT information on the patenting activity of 866 universities (HEIs) in 31 European countries over four decades (1980-2019), using citation records and patent quality indicators from OECD/STI Micro-data. KC-HEI makes possible analysis of the Institutions' innovation performance across 128 internationally comparable technological sectors and, separately, with respect to Artificial Intelligence (AI). We also develop a unique crosswalk between PATSTAT and ETER that combines KCHEI with other institution-level datasets (such as ETER and RISIS) and allows us to build a parallel dataset covering 785 patenting and 2101 non-patenting universities in Europe between 2011 and 2019. We illustrate the potential of the KC-HEI database, providing key stylised facts on the role of universities in knowledge creation, while documenting extreme core-periphery patterns of university patenting in Europe and detecting several key university-level factors that reinforce this disparity.
Keywords: O31; O33; I23; 330; Patents; Innovation; Knowledge; Higher Education Institutions; University